KEWENANGAN DINAS PERHUBUNGAN DALAM PENGATURAN LALU LINTAS DAN ANGKUTAN JALAN DI KOTA SAMARINDA - Priyo Prayogi (Universitas 17 Agustus 1945 Samarinda, 2021)
ABSTRACTThe development of the city of Samarinda is accompanied by an increase in the use of transportation facilities to support community activities and mobility. The need for the provision of supporting transportation facilities cannot stand alone through one party alone, this requires the participation of technical institutions, namely the Department of Transportation, the Police, and the Public Service. In taking action against violators, the authority of the Transportation Service is as a technical implementer according to Law Number 22 of 2009 concerning Road Traffic and Transportation that all actions that are owned and carried out must be based on statutory regulations. Such action can only be carried out by Civil Servant Investigators (PPNS) who further coordinate with the State Police Officers of the Republic of Indonesia. The problem in this writing is how the authority of the Samarinda City Transportation Service in regulating traffic and road transportation in the city of Samarinda and the obstacles faced by the Samarinda City Transportation Office in regulating road traffic and transportation in the city of Samarinda.The writing of this thesis uses Normative and Empirical research methods, namely research methods that use secondary data and primary data in assessing and tracking the regulations governing the authority of the Samarinda City Transportation Agency.Keywords: Authority, Department Of Transportation, Traffic